EPICA Dronning Maud Land pre-site survey - Karlöf, Lars; Gjerde, Knut; Winther, Jan-Gunnar (Report of the Norwegian Antarctic Research Expedition 1997/98, 1999)
Keywords: Dronning Maud Land; NARE 1997/98; geodesi; innlandsis; topografi

Geodetic and topographic work - Barstad, Bjørn; Eiken, Trond; Lytskjold, Bjørn (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: Dronning Maud Land; NARE 1992/93; geodesi; topografi

Airborne radar soundings of ice depth, GPS measurements of ice velocity and studies of landform evolution in central Dronning Maud Land East Antarctica - Näslund, Jens Ove (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; glasiologi; isstrøm; topografi

Report of the Norwegian Antarctic Research Expedition 1992/93 - Orheim, Olav (ed.) (Norsk Polarinstitutt, 1997)
Publication Title: Meddelelser
Keywords: Antarktis; NARE 1992/93; ekspedisjoner; geofysikk; geologi; glasiologi; marin biologi; marin geologi; ornitologi; oseanografi; topografi

Epica Dronning Maud Land pre site survey 1996/97 - Winther, Jan-Gunnar; Broeke van den, Michiel R.; Conrads, Louk; Eiken, Trond; Hurlen, Robert; Johnsrud, Georg; Karlöf, Lars; Onarheim, Stig; Richardson, Cecilia; Schorno, Raymond (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; akkumulasjon; innlandsis; is radar; meteorologi; snø radar; topografi

Geodetic measurements at Vestfjella and Heimefrontfjella - Barstad, Bjørn; Luktvasslimo, Brit Åse (Report of the Norwegian Antarctic Research Expedition 1993/94, 1996)
Keywords: Dronning Maud Land; NARE 1993/94; ekspedisjoner; geodesi; satellittbilder; topografi

Detailed studies of bottom freezing under an iceshelf and mapping of accumulation by use of multi-frequency pulse-aperture radar - Erlingsson, Bjørn; Gjessing, Yngvar; Hamran, Svein Erik; Holmlund, Per (Report of the Norwegian Antarctic Research Expedition 1991/92, 1994)
Keywords: Antarktis; NARE 1991/92; ekspedisjoner; georadar; isshelf; topografi

Numerical Analysis of Landsat Thematic Mapper Images of Antarctica: Surface Temperatures and Physical Properties - Orheim, Olav; Lucchitta, Baerbel K (Annals of Glaciology, 1988)
Publisher: Cambridge University Press
Keywords: Dronning Maud Land; glasiologi; innlandsis; satellittbilder; topografi

Geodetic-topographic measurements in Dronning Maud Land and on Bouvetøya - Eiken, Trond; Svendsen, Knut (Report of the Norwegian Antarctic research expedition (NARE) 1984/85, 1985)
Keywords: Bouvetøya; Dronning Maud Land; NARE 1984/85; geodesi; målinger; topografi

Norwegian Antarctic Expedition, 1968-69 - Winsnes, Thore S. (Antarctic Journal of the United States, 1969)
The aim of the Norwegian Antarctic Expedition was to carry out mapping, geological and glaciological investigations of the Kraul Mts. in western Queen Maud Land. The expedition received the assistance of the National Science Foundation in the provision of American equipment and arrangements for logistics. The six member expedition, equipped for 2 1/2 months of field operations was taken by LC-130 Hercules aircraft from McMurdo to the Kraul Mts. where on several sledge journeys, covering 800 km in all, the geology of the mountains was mapped, triangulations made and base measurements taken during Nov. 22, 1968 to Jan. 20, 1969. The geology of the Kraul Mts. is rather monotonous, consisting of amygdaloid basic-to-intermediate lavas in thick, nearly flat-lying beds. An ultrabasic olivine-rich intrusive is dominant in the westernmost part of the mountains. In the east, a small isolated outcrop con sisted of sedimentary rocks in a sequence of about 50 m, containing a fossil Glossopteris flora of Permian Age. All mountains were crossed by dolerite sills and dykes. During work in the mountains, animal and plant life were observed, and some samples were taken. Core drillings were taken at the ice shelf 70 km to the N, for comparison with main basic cores.
Coordinates: S731959 S731959 W0141000 W0141000
Keywords: Dronning Maud Land; Norwegian Antarctic Expedition 1968-69; geodesi; geologi; glasiologi; kartlegging; topografi

Besøk på Bouvetøya i 1958 og 1966 (Bouvetøya twice visited) - Winsnes, Thore S (Norsk Polarinstitutt. Årbok 1965, 1965)
Keywords: Bouvetøya; ekspedisjoner; geologi; observasjoner; topografi

Topography of South Victoria Land (Antarctic) - Bernacchi, Louis Charles (The Geographical Journal, 1901)
Publisher: [Wiley, Royal Geographical Society (with the Institute of British Geographers)]
Keywords: Antarktis; Southern Cross; Victoria Land; ekspedisjonen; ekspedisjoner; geologi; oppdagelsesreiser; topografi